To determine which pair shows equivalent expressions, we can evaluate each option:
-
−4(x + 3) = 4x - 12: Expanding the left side:
\(-4(x + 3) = -4x - 12\)
The right side is \(4x - 12\).
These are not equivalent. -
4x + 12 = −4(x − 3): Expanding the right side:
\(-4(x - 3) = -4x + 12\)
The left side is \(4x + 12\).
These are not equivalent. -
−4x − 12 = −4(x + 3): Expanding the right side:
\(-4(x + 3) = -4x - 12\)
Both sides are \(-4x - 12\).
These are equivalent. -
−4(x − 3) = −4x − 12: Expanding the left side:
\(-4(x - 3) = -4x + 12\)
The right side is \(-4x - 12\).
These are not equivalent.
The equivalent expressions are found in option 3:
−4x − 12 = −4(x + 3).